Pine Needle (Pinus densiflora) Extract-Mediated Synthesis of Silver Nanoparticles and the Preparation of Carrageenan-Based Antimicrobial Packaging Films. (27th February 2022) - Kim, Yeon Ho; Bang, Yeong-Ju; Yoon, Ki Sun; Priyadarshi, Ruchir; Rhim, Jong-Whan
Abstract : Silver nanoparticles (AgNPs) were prepared using a pine needle extract-mediated synthesis method. The X-ray diffraction (XRD) spectrum showed a characteristic peak of silver, indicating that crystalline silver nanoparticles were formed. The synthesized AgNPs were spherical and had a uniform size of 63.9 ± 2.1 nm with a narrow size distribution. The AgNPs have been used as functional nanofillers in the manufacture of carrageenan-based functional nanocomposite films. Field emission scanning electron microscopy (FE-SEM) confirmed that AgNPs were uniformly dispersed in the carrageenan polymer matrix. The addition of AgNPs to the Carr film affected the surface color, mechanical, water vapor barrier, and surface wettability properties and significantly improved the UV blocking properties of the nanocomposite films. In addition, the carrageenan/AgNP composite films showed strong antioxidant activity and potent antibacterial activity against both Gram-positive ( S. aureus ) and Gram-negative ( E. coli O157: H7) bacteria. The carrageenan/AgNP film with UV protection, antioxidant, and antibacterial activity can be used as active food packaging material to extend the shelf life of packaged food.